2018
DOI: 10.3348/jksr.2018.79.2.92
|View full text |Cite
|
Sign up to set email alerts
|

Adenosquamous Carcinoma of Duodenal Bulb Mimicking Subepithelial Tumor on Computed Tomography: A Case Report

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (https://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Only five cases of primary duodenal ASC of the non-ampulla of Vater have been reported in the English literature [ 6 – 10 ] (Table 2 ). NADASCs appear to affect both males and females, but the reported ratio of males to females is 5:1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only five cases of primary duodenal ASC of the non-ampulla of Vater have been reported in the English literature [ 6 – 10 ] (Table 2 ). NADASCs appear to affect both males and females, but the reported ratio of males to females is 5:1.…”
Section: Discussionmentioning
confidence: 99%
“…Xue et al reported only one case of NADASC in their study of 47 non-ampullary duodenal carcinomas [ 5 ]. To date, only five cases have been reported in the literature [ 6 – 10 ]. ASCs in other primary sites that normally have glandular epithelium, such as the pancreas, stomach, colon, rectum, breast, and prostate, are also rare and considered to be clinically more aggressive, with a worse prognosis than their adenocarcinoma counterparts [ 6 , 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%